An audit of cesarean section data using Robson’s classification: a study from tertiary care center in North India - Bansal, Ramandeep; Bagga, Rashmi; Monga, Anne (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Percentage of women undergoing caesarean section (CS) during childbirth continues to increase globally, more in developed than in developing countries. Accordingly, world health organization (WHO) currently recommends an acceptable rate of CS at 10-15% of total deliveries and the rate of CS may be inappropriately high in several regions of the world including India. So, we planned this study to assess, monitor and compare CS rates using Robson classification. This study aimed to apply Robson’s Ten Group Classification System (TGCS) for audit of CS and to determine contribution of each subgroup to overall CS rate to plan further interventions. Methods: This was a retrospective analysis of data collected from 1000 consecutive women undergoing CS in the department of Obstetrics and Gynecology at a tertiary care center and teaching institute in North India from January 2023 to August 2023. Results: CS accounted for 26.3% of all deliveries at our institute lower than rate reported from various other tertiary care centers in India. 35.6% of all CS were elective while the rest were performed as emergency procedures. Major contributors to CS were Robson’s groups 5, 10 and 2. The main indications for CS was fetal distress (25.3%). Considering the fact that fetal distress, breech, prior CS and refusal of TOLAC accounted for approximately 2/3rd of our CSs. Conclusions: Careful use of cardiotocography, continuous support during labor, external cephalic version for breech presentation, and proper counseling regarding TOLAC in women with prior CS can help in significant reduction in CS rates.